2008
DOI: 10.1096/fj.08-111690
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin‐interacting protein deficiency induces Akt/Bcl‐xL signaling and pancreatic beta‐cell mass and protects against diabetes

Abstract: Pancreatic beta-cell loss through apoptosis represents a key factor in the pathogenesis of diabetes; however, no effective approaches to block this process and preserve endogenous beta-cell mass are currently available. To study the role of thioredoxin-interacting protein (TXNIP), a proapoptotic beta-cell factor we recently identified, we used HcB-19 (TXNIP nonsense mutation) and beta-cell-specific TXNIP knockout (bTKO) mice. Interestingly, HcB-19 mice demonstrate increased adiposity, but have lower blood gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
242
2
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(271 citation statements)
references
References 39 publications
22
242
2
5
Order By: Relevance
“…As would be expected, induction of TXNIP by glucose was shown to promote oxidative stress and apoptosis in vascular smooth muscle cells and in the INS-1 beta cell line [9,12]. Moreover, islets from Txnip mutant mice are protected from glucose-induced apoptosis [13,14]. Thus, TXNIP is emerging as an important mediator of beta cell glucotoxicity.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…As would be expected, induction of TXNIP by glucose was shown to promote oxidative stress and apoptosis in vascular smooth muscle cells and in the INS-1 beta cell line [9,12]. Moreover, islets from Txnip mutant mice are protected from glucose-induced apoptosis [13,14]. Thus, TXNIP is emerging as an important mediator of beta cell glucotoxicity.…”
Section: Introductionmentioning
confidence: 70%
“…Nevertheless, we cannot exclude the possibility that suppression of TXNIP to a greater extent than achieved here (~50%) could enhance insulin signal transduction also in beta cells. Moreover, it was recently shown that TXNIP deficiency prevented beta cell apoptosis in vivo, protecting the animals from hyperglycaemia and hypoinsulinaemia and thereby increasing PKB/Akt signalling [14]. Therefore, enhanced insulin signalling may contribute to beta cell survival in TXNIPdeficient animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Thus, by increasing the generation and decreasing the degradation of ROS, HG-induced TxNIP may contribute to glucotoxicity, as observed by others and our group in pancreatic b cells. 13,16,17 To elucidate the role of TxNIP in the pathogenesis of DN in vivo, we explored the action of TxNIP in the diabetic kidney of wild-type (WT) and TxNIP 2/2 (knockout [KO]) mice. In streptozotocin (STZ)-induced diabetic mice we found that, unlike in WT, indicators of renal injury and dysfunction such as albuminuria, proteinuria, serum cystatin C, and serum creatinine levels were not increased in diabetic TxNIP KO mice.…”
mentioning
confidence: 99%
“…Increased Txnip expression leads to insulin-resistant glucose transport in muscle and in adipocytes (Chutkow et al 2010, Yoshihara et al 2010, and in pancreatic b cells chronic increases in Txnip expression cause apoptosis (Minn et al 2005, Chen et al 2008a,b, Corbett 2008. Hyperglycemiamediated increase in Txnip induces accelerated transcription of interleukin 1b (IL1b), in human and in mouse adipocytes, and the increased production of IL1b likely contributes to the insulin resistance of diabetes (Koenen et al 2011).…”
Section: Discussionmentioning
confidence: 99%